Fortress of the dead - Roberson, Chris (Zombie army., 2020)
Hitler is gone. Plan Z is defeated. But the Dead still walk. Jun is a deadhunter - and a damn good one. For her, patrolling Northern Italy with Sergeant Josiah and his elite squad, eradicating zombies and searching for survivors is nothing new. When the squad encounters a group of refugees being relentlessly pursued by the Dead, they uncover a new threat: a secret Alpine Redoubt stuffed with SS and Hitler Youth, who have seemingly gained control over the Dead. The race is on: neutralize the Nazi menace, destroy the secret base, and stem the tide of Dead - or lose Europe to an unstoppable zombie army. World War Two is over, but the Dead War is just beginning ...